Smoking problem in Indonesia (Medical Journal of Indonesia, 2002)
Smoking is an important public health probLem in Indonesia. Up to 60% of male adult population as well as about 4% of female adult population are smokers. In fact, some of Indonesian kretek cigarettes have quite high tar and nicotine content. Besides health effect, smoking habit also influence economic status of the individuals as well as the family. In health point of view, even though reliable nation wide morbidity and mortality data are scarce, report from various cities showed smoking related diseases, such as Lung cancer, COPD, effect of pregnancy, etc. Other problem is a fact that smoking habit start quite in early age in Indonesia. This article also describe factors complicate smoking control program as well as several things to be done to strengthen smoking control program in Indonesia. (Med J Indones 2002; 11: 56-65)Keywords : smoking, Indonesia, impact